UNDERSTANDING OF THE LEVEL OF INTEGRATION BETWEEN INDIA AND SRI LANKAN ECONOMIES WITH THE APPLICATION OF (DCC)–MGARCH (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2022)
Prime focus of this article is to check if there are  suitable diversification opportunities investing  in India. Granger causality tests, vector auto regression (VAR) and dynamic conditional  correlation (DCC)–MGARCH are applied  to investigate the level of integration between  India and Sri Lankan economies. No causality  is observed. Outcome of VAR suggest that  Sri Lankan economy does not impact the  return of the Indian stock market. Applying  DCC–MGARCH, it is observed that there is  no volatility spillover from Sri Lanka to India  in short-run but there is long run spill over of  volatility from Sri Lanka to India. The outcomes  of the study may assist market managers in  setting policies by considering the pattern of  volatility transmission from Sri Lankan stock  market to Indian stock market.
Keywords: Unit root test; VAR; Granger Causality DCC–MGARCH